The comparative study of genetic algorithm and tabu search for solving the university course timetabling problem - Siew, Li Meng, 1987-; Hishammuddin Asmuni, supervisor; Fakulti Sains Komputer dan Sistem Maklumat (2010)
Project Paper (Sarjana Muda Sains Komputer (Kejuruteraan Perisian)) - Universiti Teknologi Malaysia, 2010